Primer registro de Pseudapanteles dignus (Hymenoptera: Braconidae) como parasitoide de Tuta absoluta (Lepidoptera: Gelechiidae) en el Alto Valle de Río Negro, Argentina - Garrido, Silvina Alejandra; Cichon, Liliana I.; Lago, Jonatan D.; Aquino, Daniel A.; Vallina, Consuelo; Luna, María G. (2017)
The larval endoparasitoid Pseudapanteles dignus (Hymenoptera: Braconidae) is reported for the first time attacking the South American tomato moth Tuta absoluta (Lepidoptera: Gelechiidae) in tomato crops at Alto Valle de Río Negro, being this the most southern report for Argentina. Besides, P. dignus diagnosis and parasitism percentage arebriefly commented.